2014
DOI: 10.3855/jidc.4594
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity profiles of an adjuvanted seasonal influenza vaccine in Guatemalan children

Abstract: Introduction: The efficacy of non-adjuvanted seasonal influenza vaccine in young children is considered to be suboptimal. This study compared the safety and immunogenicity profiles of MF59-adjuvanted, trivalent, influenza vaccine (ATIV) and non-adjuvanted, trivalent, influenza vaccine (TIV) in Guatemalan children (N = 360) between 6 and < 60 months of age. Methodology: Children received two doses of ATIV or TIV administered four weeks apart. Solicited adverse reactions were recorded for seven days after each v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Seventeen trials reported seroprotection rate data (Supplementary Table 2). Fifteen trials reported SAE, neurological events, and reactogenicity data (Supplementary Tables 3-5); 14 of these 15 trials also reported seroprotection rate data) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Some trials consisted of several comparisons that assessed the same vaccines in different age groups or assessed different hemagglutinin antigen doses.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen trials reported seroprotection rate data (Supplementary Table 2). Fifteen trials reported SAE, neurological events, and reactogenicity data (Supplementary Tables 3-5); 14 of these 15 trials also reported seroprotection rate data) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Some trials consisted of several comparisons that assessed the same vaccines in different age groups or assessed different hemagglutinin antigen doses.…”
Section: Resultsmentioning
confidence: 99%
“…One phase Ib study: Study 1 (Della . Three phase II studies: Studies 2 (Vesikari et al, 2009), 3 (Solares et al, 2014), and 4 (Zedda et al, 2015). Two phase III studies: Studies 5 (Vesikari et al, 2011) and 6 (Nolan et al, 2014).…”
Section: Included Studiesmentioning
confidence: 99%
“…There are extensive data regarding the safety of MF59-adjuvanted influenza vaccines which have demonstrated an acceptable safety profile in young children ( 26 , 27 , 30 , 32 , 33 , 119 , 138 147 ). Most adverse reactions are mild-to-moderate and transient in nature and serious adverse reactions are rare.…”
Section: Safetymentioning
confidence: 99%